Alignment of Amorphous Iron Oxide Clusters: A Non‐Classical Mechanism for Magnetite Formation. Issue 13 (2nd March 2017) - Sun, Shengtong; Gebauer, Denis; Cölfen, Helmut
Abstract: Despite numerous studies on the nucleation and crystallization of iron (oxyhydr)oxides, the roles of species developing during the early stages, especially primary clusters and intermediate amorphous particles, are still poorly understood. Herein, both ligand‐free and ligand‐protected amorphous iron oxide (AIO) clusters (<2 nm) were synthesized as precursors for magnetite formation. Thermal annealing can crystallize the clusters into magnetite particles, and AIO bulk phases with domains of pre‐aligned clusters are found to be direct precursors to crystals, suggesting a non‐classical aggregation‐based pathway that differs from the reported oriented attachment or particle accretion mechanisms. Abstract : Magnetic lines : Magnetite formation via thermal annealing of amorphous iron oxide clusters proceeds from domains of pre‐aligned clusters that can be direct precursors to crystals. This phenomenon cannot be understood as oriented attachment, and seems to represent a key step in this non‐classical, aggregation‐based pathway.